PREVALENCE OF DEEP BITE IN ORTHODONTIC PATIENTS IN KANPUR POPULATION A CROSS-SECTIONAL STUDY (International Journal of Food and Nutritional Sciences, 2022)
The aim of this study was to find out the prevalence of deep bite among orthodontic patients in Kanpur city. Pre-treatment dental casts of 228 patients were selected in this study. The dental casts were assessed and according to the amount of vertical overlap of upper teeth on the labial surface of lower teeth in centric occlusion, they were divided into 3 groups: Normal over bite, deep bite and open bite. Normal over bite was found in 54% of the patients and deep bite in 38 % where as open bite was found in 8% of the patients. Half of orthodontic patients had over bite abnormality. Among the patients with deep bite, mild degree of deep bite represents majority of the cases